A Theoretical Study on the Evolution of Modern Epidemiological Concepts in Global Health Research - Mahmudi Syarif Ridho; Nouv Aqila Bages (PT Bukuloka Literasi Bangsa, 2025)
ABSTRACT This study aims to explore the theoretical evolution of modern epidemiology within the context of global health research, emphasizing its transition from traditional biomedical paradigms toward more integrative, interdisciplinary, and justice-oriented frameworks. Employing a qualitative descriptive approach through a comprehensive literature review, the research synthesizes findings from peer-reviewed articles, official reports, and theoretical sources published between 2014 and 2025. Data collection involved systematic document analysis and thematic categorization, while the analysis followed an inductive approach to identify emerging concepts and paradigmatic shifts in epidemiological theory and practice. The results reveal five major trends: (1) the persistence yet transformation of biomedical dominance; (2) methodological innovation through big data, AI, and digital epidemiology; (3) the rise of precision epidemiology integrating personalized and population-level insights; (4) the growing centrality of social justice and equity frameworks; and (5) specialized advances in wastewater-based and occupational epidemiology. These findings demonstrate how modern epidemiology is evolving into a multidimensional science that unites biological, technological, and social determinants of health. The study concludes that this evolution not only strengthens theoretical foundations but also enhances the ethical and practical capacity of global health research to address complex and inequitable health challenges. Future directions emphasize developing hybrid theoretical frameworks that balance computational innovation with social responsibility to promote global health equity. Keywords: modern epidemiology, global health, qualitative research, precision epidemiology, social determinants of health.